Study of deformation law and support design feasibility of right-angled trapezoidal roadways - Chen, Feng; Wang, Xuebin; Bai, Xueyuan (Frontiers in Earth Science, 2023)
In view of the problems of the serious asymmetric deformation and difficult support of the right angle trapezoidal roadway during the mining process, we established the mechanical model of surrounding rock of right angle trapezoidal roadway, determined the relationship between the deflection and the tilt angle of roadway roof, and made it clear that the typical failure mode of right angle trapezoidal roadway is the upper slip of high side. Two optimized support scheme are proposed, in which "constant resistance large deformation (CRLD) bolt + ordinary I-steel" or "portal energy absorbing hydraulic (PEAH) support + ordinary bolt" is used as the main support instead of "ordinary bolt + ordinary I-steel". Through numerical simulation analysis, it can be seen that the above optimized support schemes can reduce the deformation, acoustic emission (AE) quantity and AE energy of roadway surrounding rock, and change the way of surrounding rock releasing energy from "main earthquake type" to "swarm earthquake type". This shows that the two optimized schemes can effectively improve the overall bearing capacity and the integrity of the roadway surrounding rock, which can be used in field practice.